Dimensional Characteristics of Knitted Fabrics Made from 100% Cotton and Cotton/Elastane Yarns - Dereje Berihun Sitotaw (Journal of Engineering)
The dimensional characteristics such as loop length (l), wales per centimeter (wpc), courses per centimeter (cpc), stitch density (s), tightness factor (K), loop shape factor (R) and take-up rate (T) of single jersey, 1x1rib, 1x1 interlock, single pique, and two-thread fleece knitted fabrics made from 100% cotton and cotton/elastane yarns (5% elastane yarn content) are investigated in this research. Dimensional properties of knitted fabrics are an important property and determine the materials consumption during production, productions parameter, and applications of different knitted structures. The sample fabrics have been conditioned for 24 hours at 20±1°C temperature and 65±2% relative humidity. The specimens used for sampling are determined as per the test standards described in the paper for each yarn type, property, and structure. As observed in the result, the properties are related to each other. It is found that the loop length, wpc, cpc, stitch density, tightness factor, loop shape factor and take-up rate of single jersey, 1x1rib, 1x1interlock, single pique, and two-thread fleece knitted fabrics made from 100% cotton and cotton/elastane yarns are significantly influenced by the presence of an elastane yarn. The loop length of single jersey, 1x1rib, and interlock knitted fabrics made from elastane yarns reduced while the single pique and fleece increased. Similarly, other dimensional properties are significantly influenced by the yarn types used during knitting.